2019
DOI: 10.3390/soc9040069
|View full text |Cite
|
Sign up to set email alerts
|

The Convergence and Mainstreaming of Integrated Home Technologies for People with Disability

Abstract: If human rights begin in small places close to home, technologies that enable people with disability to access and control their home environments are an important human rights instrument. Smart homes exemplify recent advances in design, building construction, and integration of technologies within the built environment. They draw on multiple social and technical disciplines that share a broad vision but lack a common language, creating ambiguity and limiting the usefulness of the evidence base in determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…However, needs and expectations associated with ATs can be very specific, regarding both the type of disabilities and the particular context of a person (such as country of residence or age). Our research revealed that there are major differences for people with disabilities depending on national settings [13] and age. Users who become disabled at an older age face much more barriers related to technology use than disabled users who have been familiar with ATs since their childhood.…”
Section: Discussion: Adequate (Socio-) Technical Developments Of Atsmentioning
confidence: 77%
See 1 more Smart Citation
“…However, needs and expectations associated with ATs can be very specific, regarding both the type of disabilities and the particular context of a person (such as country of residence or age). Our research revealed that there are major differences for people with disabilities depending on national settings [13] and age. Users who become disabled at an older age face much more barriers related to technology use than disabled users who have been familiar with ATs since their childhood.…”
Section: Discussion: Adequate (Socio-) Technical Developments Of Atsmentioning
confidence: 77%
“…Irrespective of these differences, it is common that every technology development has to be accompanied by efforts regarding aiming at the social embedding of such technical solutions. Regarding the development process of technologies, there are already many approaches have already been taken underway, like universal design principles, user-centered design 5 , or participatory design, which are applied in all stages of the technological development (see, for instance, [13][14][15]), so that the decisions that are made ensure that future technologies meet the needs of people with disabilities and are well perceived by them 6 . For long, these ideas have been the core of Technology Assessment (TA) [16] and, more recently, are embraced by the prominent European paradigm of Responsible Research and Innovation (RRI) [17] and are partly addressed in the EAA.…”
Section: Discussion: Adequate (Socio-) Technical Developments Of Atsmentioning
confidence: 99%
“…In the Nordic countries, the policy emphasises using AT/WT to enable and support older people to stay and live at home [25]. For example, "smart homes" might enable older people with different impairments to participate in the daily living and increasingly use smart technology to support them with the connected technologies integrated into the buildings [26]. Other examples are primary healthcare facilities, which need to be accessible to older patients using AT/WT.…”
Section: Discussionmentioning
confidence: 99%
“…Patient experiences may be improved through smart home solutions which enable them to take control of their healthcare environment, enhance their comfort, and better communicate with family members and caregivers (Chan et al, 2009). Technologies embedded in the home envelope enable communication with and control of the home environment (Layton & Steel, 2019). Finally, smart homes enable social connectedness by connecting users to task‐ or interaction‐oriented smart devices that act as at‐home companions (i.e., socially assistive robots, pet robots, etc.)…”
Section: Incentives and Motivations Of Sht Stakeholdersmentioning
confidence: 99%